How Irrigation Systems and Tillage Regimes Shape Wheat Performance and Soil Water Balance in Semi‐Arid Pakistan: A Field–Modelling Approach - Shahid Hameed Khan Khalil; Muhammad Shahzad Khattak; Ghani Akbar; Muhammad Ajmal (Irrigation and Drainage, 2026)
Wheat productivity in semi‐arid regions is constrained by inefficient irrigation, suboptimal tillage and poor soil water management, leading to low yields and high nonproductive water losses. However, the combined effects of irrigation systems and tillage on the soil water balance remain insufficiently quantified under field conditions. This study evaluated the interactive effects of four irrigation–sowing systems—flat‐basin broadcast under flood irrigation (FBC), flat‐basin line sowing (FLC), narrow‐bed furrow irrigation (NLF) and wide‐bed drip irrigation (WLD)—and two tillage regimes (conventional tillage, CT; no‐tillage, NT) on wheat yield, water productivity and soil water balance in the Pothohar region of Pakistan using a randomized complete block design over two seasons (2023–2024 and 2024–2025). The results showed that WLD achieved the highest grain yield (up to 7.95 t ha −1 ), exceeding FBC by > 35% while reducing irrigation water use by 34%–43%. Raised‐bed systems (NLF and WLD) reduced deep percolation losses and improved soil water retention, whereas NT enhanced water productivity by > 30%. These results demonstrate that improved irrigation–sowing systems combined with no‐tillage enhance the soil water balance by reducing nonproductive losses and increasing productive water use, thereby improving wheat productivity under water‐limited conditions.